THE SUBSTANCE OF THE FORMAL PROHIBITION OF THE RIBA: ISLAMIC FINANCE AND THE TIE WITH THE REAL ECONOMY - Mustofa, Latif (Universitas Ahmad Dahlan, 2018)
Islamic Financial Institutions come up with sharia-compliant products mimicking one of their conventional counterpart. This particular development is one of the unintended consequences under the interpretation of the prohibition of interest. Islamic Finance Institutions need to find substitute for profit-generating mechanism. There is no consequential difference between ‘interestfree’ and interest-bearing products on the practical level. This paper attempts to deal with the question of the interpretation of riba on a theoretical level. This paper argues that equity-financing should be preferred to debt-financing. In doing so, this paper embraces a juristic approach to arrive at the intended conclusion. However, debt-financing could be utilised where deemed appropriate and no equity-financing method is applicable to a particular project.